Optimization of steel moment frames with panel-zone design using an adaptive differential evolution - Truong, Viet Hung (2020)
Optimization of steel moment frames has been widely studied in the literature without considering shear deformation of panel-zones which is well-known to decrease the load-carrying capacity and increase the drift of structures. In this paper, a robust method for optimizing steel moment frames is developed in which the panelzone design is considered by using doubler plates. The objective function is the total cost of beams, columns, and panel-zone reinforcement. The strength and serviceability constraints are evaluated by using a direct design method to capture the nonlinear inelastic behaviors of the structure. An adaptive differential evolution algorithm is developed for this optimization problem. The new algorithm is featured by a self-adaptive mutation strategy based on the p-best method to enhance the balance between global and local searches. A five-bay five-story steel moment frame subjected to several load combinations is studied to demonstrate the efficiency of the proposed method. The numerical results also show that panel-zone design should be included in the optimization process to yield more reasonable optimum designs.